Students’ Relational Understanding in Relations and Functions Based on Self-Esteem - Herawati, Dewi; Ekawati, Rooselyna; Rahaju, Endah Budi (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
Relational understanding has an important role in understanding mathematical concepts. With relational understanding, students are not only use the existing procedures, but also have logical reasons for the steps taken. With relational understanding, students have a stronger foundation in their understanding. When solving a mathematical problem, sometimes students are unable to remember the formula, then they can still use the concepts that they had before. This research aims to describe junior high school students' relational understanding in relations and functions based on self-esteem. This research is a qualitative descriptive research. Students were given a self-esteem scale test and a Mathematics Ability Test to select research subjects, then 3 students from class VIII-E of SMP Negeri 3 Surabaya were selected as research subjects. Then the subject was given a Mathematical Problem Solving Test, and an interview to check the subject's relational understanding. All data collected is analyzed so that the data obtained is easy to understand. The results show that subjects with high self-esteem fulfill all stages of problem solving. Subjects with medium self-esteem and subjects with low self-esteem only fulfilled two stages of problem solving. Relational understanding has an important role in understanding mathematical concepts. With relational understanding, students are not only use the existing procedures, but also have logical reasons for the steps taken. With relational understanding, students have a stronger foundation in their understanding. When solving a mathematical problem, sometimes students are unable to remember the formula, then they can still use the concepts that they had before. This research aims to describe junior high school students' relational understanding in relations and functions based on self-esteem. This research is a qualitative descriptive research. Students were given a self-esteem scale test and a Mathematics Ability Test to select research subjects, then 3 students from class VIII-E of SMP Negeri 3 Surabaya were selected as research subjects. Then the subject was given a Mathematical Problem Solving Test, and an interview to check the subject's relational understanding. All data collected is analyzed so that the data obtained is easy to understand. The results show that subjects with high self-esteem fulfill all stages of problem solving. Subjects with medium self-esteem and subjects with low self-esteem only fulfilled two stages of problem solving.